2021
DOI: 10.1002/ece3.7622
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and evolutionary patterns of Taraxacum kok‐saghyz Rodin

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Genetic mapping is essential for QTL mapping, map-based cloning, and MAS [ 29 ] and has been widely used in many major crops [ 17 , 27 , 28 , 30 ]. In the past decade, although a great quantity of TKS molecular markers (SSRs and SNPs) have been developed, they have mostly been used in research on the genetic diversity and population structure of TKS [ 7 , 20 , 21 , 23 , 24 ]. In 2016, the first TKS genetic map consisting of eight LGs was constructed, which included 1448 AFLPs, 6 COSs, 1 SSR and 63 EST-SSRs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic mapping is essential for QTL mapping, map-based cloning, and MAS [ 29 ] and has been widely used in many major crops [ 17 , 27 , 28 , 30 ]. In the past decade, although a great quantity of TKS molecular markers (SSRs and SNPs) have been developed, they have mostly been used in research on the genetic diversity and population structure of TKS [ 7 , 20 , 21 , 23 , 24 ]. In 2016, the first TKS genetic map consisting of eight LGs was constructed, which included 1448 AFLPs, 6 COSs, 1 SSR and 63 EST-SSRs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 50 SNPs were obtained from 39 transcripts related to rubber biosynthesis, and 117 SNPs were found in 36 differentially expressed gene sequences. In 2021, a total of 524,812 SNPs were obtained by genotyping-by-sequencing (GBS) and were used for population structure, genetic diversity, and evolutionary analysis of 58 wild TKS plants collected from four different regions [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [29] found that Miscanthus sacchariflorus had resistance to low acid and heavy metal toxicity, but Miscanthus sacchariflorus likes warm, moist, and semi-shady environments. Zhang et al [30] pointed out that Taraxacum koksaghyz had good tolerance to Pb and Cd stress, but its biomass was small. Taraxacum koksaghyz generally grew in alkaline environments.…”
Section: Discussionmentioning
confidence: 99%
“…The D population showed a closer genetic relationship with the C population, compared with the AB populations. A comparative analysis of the genomes of different populations showed differences in the genes involved in their adaptation to different environmental conditions [42]. In another study, high-quality genomes of the rubber-bearing TKS and the medicinal plant T. mongolicum Hand.-Mazz.…”
Section: Molecular Genetic and Genome-wide Studiesmentioning
confidence: 98%
“…In 2021, a total of 524,812 SNPs were found, based on analysis of whole genome sequencing results [42]. These SNPs were used to construct the population structure, genetic diversity, and evolutionary analysis of 58 wild TKS plants collected from four different regions.…”
Section: Molecular Genetic and Genome-wide Studiesmentioning
confidence: 99%